2009
DOI: 10.1152/ajpheart.00436.2008
|View full text |Cite
|
Sign up to set email alerts
|

Transient opening of mitochondrial permeability transition pore by reactive oxygen species protects myocardium from ischemia-reperfusion injury

Abstract: Saotome M, Katoh H, Yaguchi Y, Tanaka T, Urushida T, Satoh H, Hayashi H. Transient opening of mitochondrial permeability transition pore by reactive oxygen species protects myocardium from ischemia-reperfusion injury. Am J Physiol Heart Circ Physiol 296: H1125-H1132, 2009. First published February 6, 2009 doi:10.1152/ajpheart.00436.2008.-Reactive oxygen species (ROS) production during ischemia-reperfusion (I/R) is thought to be a critical factor for myocardial injury. However, a small amount of ROS during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 33 publications
2
65
1
1
Order By: Relevance
“…This work was also supported by the Laubisch and Kawata Endowments. also found that when transient mPTP openings are induced by Ca 2ϩ loading, mitochondrial ROS production increases markedly, which may provide a link between loss of mPTP function and loss of cardioprotection when hearts are exposed to mPTP blockers during PC episodes (6,14,15).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This work was also supported by the Laubisch and Kawata Endowments. also found that when transient mPTP openings are induced by Ca 2ϩ loading, mitochondrial ROS production increases markedly, which may provide a link between loss of mPTP function and loss of cardioprotection when hearts are exposed to mPTP blockers during PC episodes (6,14,15).…”
mentioning
confidence: 90%
“…These mice had elevated mitochondrial Ca 2ϩ content, suggesting a defect in mitochondrial Ca 2ϩ handling related to loss of mPTP function, with associated metabolic abnormalities. Second, whereas CsA given during prolonged ischemia reduces I/R injury (7), paradoxically, CsA (or sanglifehrin A) administered during ischemic or pharmacologic PC episodes blocks cardioprotection (6,14,15). This finding is reminiscent of reactive oxygen species (ROS), in which ROS scavengers given during prolonged ischemia reduce I/R injury, but ROS scavengers given during ischemic or pharmacologic PC episodes block cardioprotection (16).…”
mentioning
confidence: 99%
“…Originally, VDAC was considered to be a crucial component of this canal but was ruled out later because the intrinsic apoptotic pathway was also induced in VDAC knockout mice (13). Currently, Halestrap et al (56) propose that mPTP is composed of adenine nucleotide translocase, mitochondrial phosphate carrier, and their regulator cyclophilin-D. Ca 2ϩ overload (57) or ROS (175) is crucial to open the pore that enables small molecules to pass between the mitochondrial matrix and cytosol, allowing for an H ϩ influx into mitochondria. This cancels the membrane potential across the mitochondrial membrane and results in mitochondrial swelling and subsequent apoptotic changes (66).…”
Section: Factors Underlying the Mechanisms Of Preconditioningmentioning
confidence: 99%
“…Akt activation and TUDCA themselves did not exhibit any effect on mitochondrial membrane potential and NAD + content. To further evaluate the role of mPTP opening and GSK3b in ER stress-induced mitochondrial damage, cardiomyocytes from WT mice were treated with tunicamycin (3 lg/ml) for 5-6 h in the absence or presence of the mPTP inhibitor cyclosporin A (200 nM) (41) or the GSK3b inhibitor SB216763 (10 lM) (13) before the assessment of mitochondrial function. Intriguingly, both cyclosporin A and SB216763 were capable of preventing tunicamycin-induced loss of …”
Section: Effect Of Akt Activation On In Vitro Er Stress-induced Changmentioning
confidence: 99%
“…To further evaluate the role of GSK3b and mPTP opening in ER stress-induced cardiac contractile dysfunction, murine cardiomyocytes from WT mice were treated with tunicamycin (3 lg/ml) for 5-6 h in the absence or presence of the mPTP inhibitor cyclosporine A (200 nM) (41) or the GSK3b inhibitor SB216763 (10 lM) (13) before assessment of cardiomyocyte mechanical function. The ER stress chaperon TUDCA (500 lM) was used as a positive control (11).…”
Section: Effects Of Inhibition Of Mptp and Gsk3b On Er Stress-inducedmentioning
confidence: 99%